Elastic Properties and Phonon Dispersion of bcc Vanadium under Pressure from First Principles (Journal of Atomic and Molecular Sciences, 2014)
We investigate the elastic properties and phonon dispersion of the body-centeredcubic structure vanadium $(V)$ under pressure by using the generalized gradientapproximation (GGA). Our elastic constants of $V$ at zero pressure and zero temperatureare in good agreement with the available experimental data and other theoreticaldata. The pressure dependences of bulk modulus $B$ and its pressure derivative $B',$ shear modulus $G,$ elastic Debye temperature $Θ_E,$ elastic anisotropy factor $A,$ Poissonratios $σ$ and Kleinmann parameter $ζ$ are also presented. An analysis for the calculatedelastic constants has been made to reveal the mechanical unstability of $V$ up to 100GPa. For the phonon dispersions of $V,$ it is easily seen that the phonon frequenciesincrease as the volume decreases, the phonon mode linked to a Kohn anomaly hassoftened to negative values.
Keywords: vanadium; elastic properties; phonon dispersion; density functional theory.